Synergistic effect of mannan extracted from Saccharomyces cerevisiae with antibiotics against multidrug resistant Escherichia coli (Journal of the College of Basic Education, 2024)
Multidrug-resistant Escherichia coli (MDR-E. coli) presents a formidable healthcare challenge, continuously evolving resistance to conventional antibiotics. The aim of this study focuses on assessing the synergistic effect and enhance the effectiveness of traditional antibiotics of mannan extracted from Saccharomyces cerevisiae on MDR-E. coli. Clinical samples (n=150) were collected from several hospitals in Baghdad for both sexes between August and December 2022, including 73 urine, 10 catheter, 13 wound, and 54 stool samples. Among the total collected samples, 112 E. coli isolates were obtained, with 54 derived from urine, 9 from catheter samples, 6 from wound samples, and 43 from stool samples. Antimicrobial susceptibility test (AST) revealed resistance to imipenem (0%) and amikacin (2%), with sensitivity observed for cefotaxime (25%), gentamicin (29%), ceftriaxone (28%), ciprofloxacin (41%), norfloxacin (34%), trimethoprim-sulfamethoxazole (48%), and tetracycline (35%). Mannan purified from S. cerevisiae demonstrated inhibitory effects on E. coli growth, with Minimum Inhibitory Concentrations (MIC) ranging from 100 to 12.5 mg/mL and Minimum Bactericidal Concentrations (MBC) from 25 to 200 mg/mL. Furthermore, mannan exhibited a synergistic effect with conventional antibiotics, pointedly boosting the efficacy of gentamicin (250%), cefotaxime (160%), ceftriaxone (340%), ciprofloxacin (344.4%), norfloxacin (337.5%), and trimethoprim-sulfamethoxazole (237.5%). This research addresses the public health threat posed by MDR-E. coli, highlighting the potential of S. cerevisiae mannan as a promising solution for inhibiting E. coli and improving antibiotic efficacy.